2019
DOI: 10.14295/cs.v10i3.2604
|View full text |Cite
|
Sign up to set email alerts
|

Partition and macronutrients accumulation in pineapple under nitrogen doses and plant density

Abstract: Studies related to the absorption and exportation capacity of macronutrients by irrigated pineapple are essential for the definition of adequate doses and fertilization management. The objective of this study was to evaluate the accumulation of biomass and macronutrients in the compartments (leaves, shoot, root, seedlings/slip, crown/top, and fruit) of ‘Vitória’ pineapple irrigated in the semiarid region after the use of nitrogen doses and population densities. The treatments, arranged in randomized blocks wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
(1 reference statement)
1
3
0
Order By: Relevance
“…The accumulated K in crop residues per hectare was 1.55 Mg. This confirms that K is the most required macronutrient by pineapple plants (Pegoraro et al, 2014b;Souza et al, 2019) and denotes the need for a correct management of this residue to avoid high nutrient losses in the area, which affects soil fertility, resulting in economic and environmental losses.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The accumulated K in crop residues per hectare was 1.55 Mg. This confirms that K is the most required macronutrient by pineapple plants (Pegoraro et al, 2014b;Souza et al, 2019) and denotes the need for a correct management of this residue to avoid high nutrient losses in the area, which affects soil fertility, resulting in economic and environmental losses.…”
Section: Resultssupporting
confidence: 57%
“…Macronutrient accumulation in the crop residues of the cultivars IAC-Fantástico, Pérola, and Smooth Cayenne was, in decreasing order: N > K > Ca > Mg > S > P. The largest part of absorbed and accumulated nutrients is found in the leaves, and the lowest in the roots. The quantity of exported nutrients by pineapple plants is relatively high (Souza et al, 2019), which are those immobilized by fruits and propagative organs, and is even higher in cultivars that present higher harvest index.…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation
“…For these practices, the K/N ratio is below or above the recommended dose and leads to a reduction in crop yield and fruit quality (Sossa et al, 2017;Djido et al, 2021). The low planting density contributes to low yields (de Souza et al, 2019;Sanya et al, 2020). Djido et al (2021) showed that, high planting density does not influence the weight of the fruits.…”
Section: Discussionmentioning
confidence: 99%
“…The cultivar used influences plant size, nutrient absorption, dry matter production, fruit yield and dry matter accumulation in the different organs of the plant (Hanafi et al, 2009;Neri et al, 2021); which affects the concentration and accumulation of nutrients in each part of the plant (Sampaio et al, 2011;Trejo et al, 2020). Planting density is another factor that can affect the concentration of nutrients because it modifies the size of the plant; as the plantation density increases, the number of leaves emitted, the size of the stem and the size of the fruit are reduced (Cardoso et al, 2013;Souza et al, 2019). Although a smaller size and amount of dry matter is obtained from the plant in the highest planting density, the yield, and the amount of dry matter per hectare is greater as the planting density increases, consequently, the amount of nutrient extracted per hectare increases as the amount of dry matter produced increases (Souza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%